2001
DOI: 10.1037/0022-3514.81.5.828
|View full text |Cite
|
Sign up to set email alerts
|

Imagining stereotypes away: The moderation of implicit stereotypes through mental imagery.

Abstract: Research on implicit stereotypes has raised important questions about an individual's ability to moderate and control stereotypic responses. With few strategies shown to be effective in moderating implicit effects, the present research investigates a new strategy based on focused mental imagery. Across 5 experiments, participants who engaged in counterstereotypic mental imagery produced substantially weaker implicit stereotypes compared with participants who engaged in neutral, stereotypic, or no mental imager… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
471
5
11

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 528 publications
(502 citation statements)
references
References 65 publications
15
471
5
11
Order By: Relevance
“…Numerous strategies have been proposed for reducing implicit prejudices (e.g., intergroup contact (Turner & Crisp, 2010), counter-stereotypic imagery (Blair, Ma, & Lenton, 2001), exposure to counter-stereotypic exemplars (Dasgupta & Greenwald, 2001)). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous strategies have been proposed for reducing implicit prejudices (e.g., intergroup contact (Turner & Crisp, 2010), counter-stereotypic imagery (Blair, Ma, & Lenton, 2001), exposure to counter-stereotypic exemplars (Dasgupta & Greenwald, 2001)). …”
Section: Discussionmentioning
confidence: 99%
“…This generalisation requires reconciliation (and thus elaborative processing) of a positive experience with a negative out-group attitude. Likewise, imagery (Blair et al, 2001) and consideration of counter-stereotypic exemplars (Dasgupta & Greenwald, 2001) both explicitly require individuals to elaborate upon counter-stereotypic information. Hence, encouraging elaborative processing (particularly among those who are not naturally disposed to it) may have added benefits when it comes to effectively reducing implicit prejudice.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, IAT measures of racial attitudes indicate that White participants are less prejudiced against Black persons (a) when interacting with a Black experimenter than when interacting with a White experimenter (e.g., Lowery, Hardin, & Sinclair, 2001); (b) after seeing movie clips of Black individuals in a positive compared with a negative situational context (e.g., Wittenbrink, Judd, & Park, 2001); or (c) after seeing pictures of admired Black individuals and disliked White individuals compared with pictures of disliked Blacks and admired Whites (e.g., Dasgupta & Greenwald, 2001). In studies on gender stereotypes, Blair, Ma, and Lenton (2001) showed that gender stereotypes as measured by IAT effects were less pronounced following counterstereotypic mental imagery but were stronger following stereotypic mental imagery. Note, however, that there is disagreement about whether these malleability effects provide evidence for the validity of IAT scores.…”
Section: Iat Effects the What Criterion: What Attributes Cause Variatmentioning
confidence: 99%
“…Until more recently, the commonly accepted assumption was that beliefs about others were inflexible (Dovidio & Fazio, 1992;Fazio, Jackson, Dunton & Williams, 1995), however, newer research suggests that in the presence of counter-stereotypic information beliefs are susceptible to malleability (Blair, Ma & Lenton, 2001;Dasgupta & Greenwald, 2001). In particular, studies around impression formation show that when individuals exhibit characteristics that set them apart from others in their group, the generalised group beliefs are less likely to apply to that individual (Livingston & Brewer, 2002;Macrae, Mitchell & Pendry, 2002).…”
Section: Offenders' Racementioning
confidence: 99%